An interpetation of the methodic doubt by E. Husserl and J.-P. Sartre: transcendental and transcendent ego in the theory of intersubjectivity - Burlachenko, Tetyana (Actual Problems of Mind, 2017)
The author compares the interpretations of Cartesian’s methodic doubt and its agent (ego cogito) in the phenomenological projects by E. Husserl and J.-P. Sartre in accordance with their understanding of the nature of intersubjective connection between distinct thinking Selves.